Top management capabilities and performance of halal product - Mazida Ismail; Norhidayah Mohamad; Amiruddin Ahamat (Innovation & Management Review, 2020)
Purpose - The purpose of this study is to investigate the influence of top management capabilities inclusive of global mindset (GM), foreign knowledge (FK) and international firm performance (IP). Design/methodology/approach This paper opted for a descriptive study using structured questionnaires involving 118 Malaysian small medium enterprises (SMEs) that are currently marketing their products abroad with halal JAKIM certification. Multiple regression analysis was applied to test the influence of the two variables on international performance. Findings The findings revealed both GM and FK significantly influence IP, which is crucial to overcome SMEs' resistance to go international. Research limitations/implications This study only focusses on the niche market which is halal export product, thus the findings may not be generalized to other sectors. Furthermore, the firm size might also influence the significant contribution of top management. Originality/value This paper is a part of ongoing study of internal capabilities and international firm performance among SMEs halal product manufacturers in developing countries.
Keywords: 650; Halal; Internationalization; Performance; Top management capabilities